1980
DOI: 10.1007/bf00255461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mode(s) of action of a new series of imide derivatives of 3-nitro-1,8 naphthalic acid

Abstract: Four new imide derivatives of 3-nitro-1,8-naphthalic acid have been synthesised. The compounds show strong cytostatic activity against both HeLa and KB cells and are moderately toxic towards both mice and rats (LD50 above 4 mg/kg IP). Two of the most active compounds, M-4212 and M-12210, prevented the development of mouse Ehrlich ascites and rat Yoshida carcinoma. All these drugs block cell growth by inhibiting the synthesis of both DNA and RNA. In particular, both M-4212 and M-12210 raise the melting point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 4 publications
1
48
0
Order By: Relevance
“…1,8-Naphthalimide and bisnaphthalimide derivatives are promising anticancer agents [9,10], the sulfonated derivatives are good antiviral agents with selective in vitro activity against the human immunity deficiency virus, HIV-1 [11]. Due to their photo-physical and photo-chemical properties the 1,8-naphthalimide derivatives can be used as fluorescence dyes for solar energy collectors and photosynthesis under concentrated sunlight [12], fluorescent markers in biological cells [13] as well as laser active media [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1,8-Naphthalimide and bisnaphthalimide derivatives are promising anticancer agents [9,10], the sulfonated derivatives are good antiviral agents with selective in vitro activity against the human immunity deficiency virus, HIV-1 [11]. Due to their photo-physical and photo-chemical properties the 1,8-naphthalimide derivatives can be used as fluorescence dyes for solar energy collectors and photosynthesis under concentrated sunlight [12], fluorescent markers in biological cells [13] as well as laser active media [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In continuing phase I studies of amonafide reported recently [4,5], amonafide at a dosage up to 260 mg/m2/day • 5 days resulted in no significant myelosuppression, its peak plasma level being 6 /zg/ml [5]. The drug's mechanism of action is believed to be DNA intercalation [6], and it does not require in vivo activation to exert the antitumor effect [1,7]. Amonafide will soon be investigated further in phase II studies in the United States.…”
Section: Introductionmentioning
confidence: 97%
“…Benzisoquinolinedione, 5-amino-2 [2-(dimethylamino) ethyl]-1H-benz [de]isoquinoline-1,3(2H)-dione (amonafide, previously named nafidamide) is one of a series of benz[de]-isoquinoline-l,3-dione compounds recently demonstrated to possess antitumor and antiviral activities [1][2][3]. Amonafide was found by the National Cancer Institute (NCI) to be active against P388 and L1210 leukemia, as well as B16 melanoma and M5076 sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…1B). Brana et al reported bisnaphthalimides as potent chemotherapeutic agents [26][27][28][29]. Bisnaphthalimide derivatives are identified to possess significant anti-tumour activity in both murine and human cancerous cells [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%